Characterizing the macroscopic response and local deformation mechanisms of a unidirectional non-crimp fabric. (May 2022) - Ghazimoradi, Mehdi; Trejo, Eleazar A.; Butcher, Clifford; Montesano, John
Abstract: The macroscopic response and local deformation mechanisms of a warp stitched heavy-tow unidirectional non-crimp fabric (UD-NCF) was characterized. Quasi-static uniaxial tests captured the fabric in-plane longitudinal, transverse, and shear deformation response where digital image correlation was employed. The fabric bending response was captured through modified cantilever tests. Off-axis extension tests conducted along 30°, 45° and 60° bias directions revealed that extension and contraction of the polyester stitching web and resulting transverse compression of the carbon fiber tows and inter-tow sliding were the dominant local deformation mechanisms. At a bias angle of 30°, the extent of inter-tow sliding increased when compared to a bias angle of 45° leading to earlier onset of fabric shear locking, while at a bias angle of 60° shear locking also occurred sooner. Shear angle maps and strain profiles at different bias angles further revealed the notable inter-dependency between the fabric shear, longitudinal and transverse deformations, which was governed by the interactions between the stitching and carbon fiber tows. The distinct out-of-plane bending behavior of the fabric reinforcement along longitudinal and transverse directions was also captured and quantified. The study provided a comprehensive characterization of the UD-NCF, which is critical for the development of constitutive models.